2018
DOI: 10.1002/cpp.2331
|View full text |Cite
|
Sign up to set email alerts
|

Self‐practice/self‐reflection as an alternative to personal training‐therapy in cognitive behavioural therapy training: A qualitative analysis

Abstract: The themes found equivalents in existing goals of traditional therapists' training-therapy. Though brief, SP/SR may be a credible alternative/adjunctive training-therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…These findings are consistent with the existing SP/SR literature (Bennett-Levy, 2019;Bennett-Levy et al, 2001;Chigwedere et al, 2019;Gale and Schröder, 2014;McGillivray et al, 2015;Spendelow and Butler, 2016). For instance, Bennett-Levy et al (2001) found in their initial study that SP/SR training led to a greater understanding of the cognitive model and its process of change.…”
Section: Declarative and Procedural Learningsupporting
confidence: 87%
See 3 more Smart Citations
“…These findings are consistent with the existing SP/SR literature (Bennett-Levy, 2019;Bennett-Levy et al, 2001;Chigwedere et al, 2019;Gale and Schröder, 2014;McGillivray et al, 2015;Spendelow and Butler, 2016). For instance, Bennett-Levy et al (2001) found in their initial study that SP/SR training led to a greater understanding of the cognitive model and its process of change.…”
Section: Declarative and Procedural Learningsupporting
confidence: 87%
“…Specifically to anxiety and exposure interventions, McGillivray et al (2015) noted that the literature has demonstrated that SP/SR promotes an increased understanding of avoidant and compensatory behaviours in maintaining dysfunction. The enhanced understanding of techniques and their limitations has also been reported previously (Chigwedere et al, 2019;Gale and Schröder, 2014;McGillivray et al, 2015), and has been shown to enhance therapists' ability to flexibly adapt such techniques (Gale and Schröder, 2014;McGillivray et al, 2015).…”
Section: Declarative and Procedural Learningmentioning
confidence: 66%
See 2 more Smart Citations
“…This can indeed increase the risks mentioned above. Self-practice, self-reflection (Chigwedere et al, 2019) and the critical incident analysis model can be useful tools for these therapists. A survey of compassion satisfaction, burnout and secondary traumatic stress of British therapists working with traumatized individuals reported that a higher risk of secondary traumatic stress was predicted in therapists engaging in more individual supervision and self-care activities and those with a personal trauma history (Sodeke-Gregson et al, 2013).…”
Section: Summary and Discussionmentioning
confidence: 99%